Loss-Driven Activism - Elia, Marco (Journal of Financial and Quantitative Analysis, 2024)
Abstract I show that hedge funds react to unrealized losses on their passive positions by engaging with the management. The hedge fund managers’ psychological response is consistent with cognitive dissonance: They blame the firms’ management and switch to activism. The loss, which is hedge fund-investment specific, is distinct from economic factors such as the firm’s industry-adjusted performance. Loss-driven activism is more likely to be unfocused on specific issues and results in worse firm performance. This study shows that an overlooked consequence of unrealized losses is to trigger an active engagement with the firm.